Yeasts in the attine ant–fungus mutualism: Diversity, functional roles, and putative biotechnological applications - Bizarria, Rodolfo [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Rodrigues, Andre [UNESP] (Wiley, 2022)
Insects interact with a wide variety of yeasts, often providing a suitable substrate for their growth. Some yeast–insect interactions are tractable models for understanding the relationships between the symbionts. Attine ants are prominent insects in the Neotropics and have performed an ancient fungiculture of mutualistic basidiomycete fungi for more than 55–65 million years. Yeasts gain access to this sophisticated mutualism, prompting diversity, ecological, and biotechnological studies in this environment. We review half a century research in this field, surveying for recurrent yeast taxa and their putative ecological roles in this environment. We found that previous studies mainly covered the yeast diversity from a small fraction of attine ants, being Saccharomycetales, Tremellales, and Trichosporonales as the most frequent yeast or yeast-like orders found. Apiotrichum, Aureobasidium, Candida, Cutaneotrichosporon, Debaryomyces, Meyerozyma, Papiliotrema, Rhodotorula, Trichomonascus, and Trichosporon are the most frequent recovered genera. On the other hand, studies of yeasts’ ecological roles on attine ant–fungus mutualism only tapped the tip of the iceberg. Previous established hypotheses in the literature cover the production of lignocellulosic enzymes, chemical detoxification, and fungus garden protection. Some of these roles have parallels in biotechnological processes. In conclusion, the attine ant environment has a hidden potential for studying yeast biodiversity, ecology, and biotechnology, which has been particularly unexplored considering the vast diversity of fungus-growing ants.
Keywords: Attina; biotechnology; mycobiome; symbiosis; yeast diversity; yeast–insect symbiosis